Artificial Intelligence: Innovation and Midwifery Education, Practice, And Research in Arab Region; Systematic Review Based Findings - Sahar M. Yakout; Ibtesam Jahlan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Artificial intelligence innovation is defined as highly specialized productive and generalizable practices in every field of life. In the healthcare setting artificial intelligence has certain revolutions associated with the linkage of healthcare practices to provide humankind with effective healthcare interventions. Midwifery operationalizing the artificial intelligence innovation to enhance them is knowledge competencies and skills regarding the process of restoration and after a birth period.Aim: To evaluate the literature based on artificial intelligence innovation to midwifery education, practice, and research in the Arab region.Method: A systematic review of rationalize the fundamental strategies of Kitchenham systematic review procedure. The data collected from the Arab region published period articles from 2019 to 2023. The process involves the identification, screening, eligibility identification, and inclusion of the studies with respect to the desired concern.Results: As 15 articles were selected out of 1000,850. Selection of the study based on identified criteria of the selection confidence interval of 95% with a margin of error of 5%.Conclusion: Artificial intelligence has more significant work to do with the education practice and research in the paradigm of midwifery it focuses largely on identifying potential health concerns associated with the new advanced technology. Operationalization of machine learning at deep learning is one of the basic consequences through which the higher extent of health prognosis is developed to understand the health promotional parameter.